Rice Field Pawning Practices from the Perspective of Fiqh Muamalah: A Study in Langen Sari Village, Karang Tengah, Cianjur - Faisal Tanjung; Muhammad Mushab; Refki Saputra (Civiliza Publishing, 2026)
Rahn (Islamic pawn financing) is an instrument in Islamic commercial jurisprudence (fiqh muamalah) that functions as debt collateral while protecting the rights of parties involved in financial transactions. Although the concept of rahn has been widely developed within Islamic financial institutions, traditional rice field pawning practices remain common in rural communities and often diverge from the normative principles of Islamic law. This study analyzes rice field pawning practices in Langen Sari Village, Karang Tengah District, Cianjur Regency, evaluates their conformity with fiqh muamalah principles, and identifies their legal and ethical implications. A qualitative case study approach was employed, with data collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the practice is conducted through oral agreements without written contracts or a clearly defined repayment period. The creditor (murtahin) is granted the right to manage the land and receive all harvest yields until the debt is repaid. Although the essential pillars of rahn are fulfilled, the practice is not fully consistent with Islamic legal principles due to elements of uncertainty (gharar) and unequal benefit favoring the creditor. The study concludes that local traditions and economic necessity shape the practice more strongly than formal Islamic legal understanding, highlighting the need for greater fiqh muamalah education and a more transparent, equitable, and Sharia-compliant model of agricultural pawning.